Factors limiting the utility of bronchoalveolar lavage in the diagnosis of COVID-19. Issue 5 (5th November 2020) - Aggarwal, Deepak; Saini, Varinder
We read with interest study by Geri et al. [1], in which the authors have demonstrated a strong agreement between negative nasopharyngeal (NPs)/nasal (Ns) swab and bronchoalveolar lavage (BAL) real-time reverse transcriptase-polymerase chain reaction (rRT-PCR) in the diagnosis of coronavirus disease 2019 (COVID-19) among hospitalised patients. The study findings contradicted earlier reports [2] and suggested a limited utility of BAL. However, the results need to be interpreted comprehensively before drawing any conclusion. Bronchoalveolar lavage has a specific place in the diagnosis of COVID-19. The clinical performance of BAL rRt-PCR is dynamic in nature and depends on different clinical and demographic factors. https://bit.ly/3aZUAPB